Employee Performance Analysis: The Role of Compensation, Training and Motivation - Mohammad Hanafi Khoiron (Dinasti International Journal of Education Management And Social Science, 2023)
Employee Performance Analysis: Compensation, Training and Motivation is a scientific article in the literature study within the scope of Human Resource Management. The purpose of this article is to build a hypothesis on the relationship between variables that will be used in future research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The library research method, from e-books and open access e-journals. The result of this article is that: 1) Compensation plays a role in implementation employee performance; 2) Role training in implementation employee performance; and 3) Role motivation in the implementation of employee performance.